Exonuclease I of Saccharomyces cerevisiae functions in mitotic recombination in vivo and in vitro. - Fiorentini, P (1997)
We previously described a 5'-3' exonuclease required for recombination in vitro between linear DNA molecules with overlapping homologous ends. This exonuclease, referred to as exonuclease I (Exo I), has been purified more than 300-fold from vegetatively grown cells and copurifies with a 42-kDa polypeptide. The activity is nonprocessive and acts preferentially on double-stranded DNA. The biochemical properties are quite similar to those of Schizosaccharomyces pombe Exo I. Extracts prepared from cells containing a mutation of the Saccharomyces cerevisiae EXO1 gene, a homolog of S. pombe exo1, had decreased in vitro recombination activity and when fractionated were found to lack the peak of activity corresponding to the 5'-3' exonuclease. The role of EXO1 on recombination in vivo was determined by measuring the rate of recombination in an exo1 strain containing a direct duplication of mutant ade2 genes and was reduced sixfold. These results indicate that EXO1 is required for recombination in vivo and in vitro in addition to its previously identified role in mismatch repair.